Learning Transformation: Optimizing Student Potential Through Inclusive and Meaningful Differentiated Learning - Wahyuni, Sri; Khoiri, Nur (FKIP Universitas Lampung, 2023)
Differentiated learning is an approach designed to meet the different learning needs of each student. This method involves adjusting methods, materials and assessments in three aspects: content, process and product. Although interest in differentiated learning is increasing, its implementation is still a challenge for teachers and educational institutions. Previous literature studies have explored the implementation and potential of differentiated learning. This study aims to present a literature review with a focus on previous articles on the implementation of differentiated learning. The results of the analysis of 82 articles show that this approach can be integrated with various learning models and can improve student learning outcomes and their enthusiasm for learning. In addition, it resulted that there is the potential for differentiated learning to be carried out in the context of strengthening the profile of Pancasila students. With a better understanding of differentiated learning, it is hoped that an inclusive and meaningful learning experience will be created for every student. Keywords: differentiated learning; inclusiveness of learning; optimization of student potential; independent curriculum; student learning outcomes DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp453-466